Modeling the Determinants of Hotel Service Booking During COVID-19 - Pal, Garima; Pandey, Ashutosh (Indian Journal of Marketing, 2023)
The COVID-19 pandemic caused a massive fall in demand and revenues and changed consumers’ perceptions and expectations. Recovery from such a scenario demands attention from researchers, industry practitioners, and hotel management. This paper explored how online reviews, hotel trust, brand image, and perceived health risks affected consumers’ hotel booking intentions during COVID-19. The cross-sectional study included 319 participants. Using PLS-SEM, the results showed that all factors affected hotel booking intention, except perceived health risk. The results can be helpful for managerial implications as they identified the critical factors for enhancing the hotel booking intention among prospective customers during the COVID-19 pandemic.